Production Of Activated Carbon From Sawdust Using Fluidized Bed Reactor. - Man, Kee Lam; Zakaria, Ridzuan (2008)
Activated carbon was produced from sawdust by using steam activation in a high temperature muffle furnace. Fast pyrolysis process was carried out prior in fluidized a bed furnace to produce char before activation process.